PULSE WAVE VELOCITY AND ITS USEFULNESS IN ESTIMATION OF HYPERTENSION - T, JAYANTHI; M, Anburajan (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: Arterial vessel wall stiffnessâ€ is an important determinant of cardiovascular disease (CVD). Prolonged hypertension causes deterioration in the blood vessel elasticity. Hypertension can be prevented by early diagnosis. Pulse wave velocity (PWV) is the direct method for assessing the arterial stiffness. Though numerous studies have been performed, the definite limit is not declared to evaluate CVD based on the threshold of PWV for South Indian population. Methods: In this study, we included a total of 246 healthy controls and 14 hypertensive patients. Mechanical variables of blood flow are measured using PC-based periScope Device (Genesis Medical Systems, India). The following variables are measured from the normal controls and hypertensive patients: (i) Heart rate (bpm), (ii) systolic blood pressure (SBP) (mmHg), (iii) diastolic blood pressure (DBP) (mmHg), (iv) brachial PWV (baPWV) (cm/s), (v) carotid-femoral PWV (C-F PWV) (cm/s), (vi) pulse pressure (mm Hg), (vii) arterial stiffness index (ASI) (mmHg), (viii) anklebrachial index (ABI), (ix) aortic SBP and DBP (mmHg), and (x) aortic augmentation pressure (mmHg). Results: The study shows the deterioration in the vessel elasticity with advancing age in both men and women. In the normal men population studied (n=135), an increase in SBP from a young age to older age was 3.7%, likewise in women (n=111), it was 12%. A standard cutoff value of 1738 cm/s for baPWV and 1215 cm/s for C-F PWV was calculated from the combined group of known hypertensive patients and age- and sex-matched normal controls. Conclusion: Thus, the PWV and the variables derived from it can be used for evaluating the status of blood vessels noninvasively. Keywords: Vascular stiffness, Pulse wave velocity, Gender, Carotid-femoral, Hypertensive.